Tren, Tema, dan Jaringan Konseptual Teknologi Imersif dalam Pembelajaran Sains Kuantum: Analisis Bibliometrik - Muhammad Musyaddad; Lilik Hasanah; Ahmad Aminudin (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
This study presents a bibliometric analysis of research on immersive technologies in quantum-related education, based on 32 Scopus-indexed publications published between 2017 and 2025. The dataset was obtained through a structured search and screened using predefined inclusion and exclusion criteria, focusing on empirical studies implementing immersive technologies (e.g., virtual reality, augmented reality, and extended reality) in quantum-related learning contexts. The analysis was conducted using Bibliometrix and Biblioshiny, applying techniques such as publication trend analysis, country productivity mapping, keyword co-occurrence, and thematic analysis. The results show a steady increase in the number of scientific publications, with the United States, Indonesia, and China emerging as major contributors. Keyword co-occurrence analysis and thematic mapping identified virtual reality and augmented reality as dominant themes, reflecting their central role in supporting visualization and learning processes. Trend analysis also indicates increasing attention to virtual laboratories and modern physics contexts. However, given the relatively small size of the dataset, these findings should be interpreted with caution and viewed as early indications of a developing research domain, rather than as definitive trends. Overall, this study highlights the growing importance of immersive technologies in addressing representation challenges in quantum science education and identifies opportunities for deeper conceptual integration, methodological diversification, and interdisciplinary collaboration in future research.